Розрахунок електромагнітного потенціалу в системі зі складними граничними умовами - Савченко, С. О.; Грицунов, О. В. (ХНУРЕ, 2019)
The report discusses the results of modeling the distribution of the azimuthal component of the high-frequency magnetic field, the radial and axial components of the electric field in the space of a cylindrical system with azimuthal symmetry.
Keywords: Розрахунок електромагнітного потенціалу; Розрахунок електромагнітного потенціалу в системі зі складними граничними умовами